2006
DOI: 10.1074/jbc.m607244200
|View full text |Cite
|
Sign up to set email alerts
|

Decorin Modulates Fibrin Assembly and Structure

Abstract: . We now report that the decorin-fibrinogen interaction alters the assembly, structure, and clearance of fibrin fibers. Relative to fibrinogen, substoichiometric amounts of decorin core protein modulated clotting, whereas an excess of an active decorin peptide was necessary for similar activity. These concentration-dependent effects suggest that decorin bound to the D regions sterically modulates fibrin assembly. Scanning electron microscopy images of fibrin clotted in the presence of increasing concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 80 publications
1
28
1
1
Order By: Relevance
“…Similarly, decorin and biglycan, proteoglycans involved in the purported inhibition and/or regulation of collagen fibril and fibrin assembly (10,12,43), demonstrated a significantly greater expression in the 7-wk HLU-group compared with the Amb-healing group, suggesting that normal fibrillogenesis in the HLU-healing animals may be compromised. The importance of decorin gene and protein expression in ligament healing needs further study.…”
Section: Differential Expression Extracellular Matrix Genes During LImentioning
confidence: 98%
“…Similarly, decorin and biglycan, proteoglycans involved in the purported inhibition and/or regulation of collagen fibril and fibrin assembly (10,12,43), demonstrated a significantly greater expression in the 7-wk HLU-group compared with the Amb-healing group, suggesting that normal fibrillogenesis in the HLU-healing animals may be compromised. The importance of decorin gene and protein expression in ligament healing needs further study.…”
Section: Differential Expression Extracellular Matrix Genes During LImentioning
confidence: 98%
“…1 Variables known to influence fibrin clot structure include fibrinogen and thrombin concentrations, 1 pH, 2,3 ionic strength, 3 chloride ion concentration, 2 and presence of calcium ions. 4 A variety of molecules are reported to affect fibrin clot structure, including homocysteine, 5 decorin core protein, 6 heparins, 7,8 dextran, 9 and hydroxyethylstarch. 10 In this study, we demonstrate that inorganic polyphosphate (polyP) strongly modulates fibrin clot structure.…”
Section: Introductionmentioning
confidence: 99%
“…Recently described examples include the decorin and platelet factor-4. 35,36 Furthermore, STAT5 is known to be involved in a number of signaling pathways including prolactin, interleukin-2 (IL-2), IL-3, IL-5, insulin, and epidermal growth factor signaling. Others have shown that there are dramatic changes in the expression of genes/proteins in the livers of STAT5-deficient mice.…”
Section: Discussionmentioning
confidence: 99%